Calibration of possum density estimates from raised leghold traps - Thomas, M.; Brown, J.A. (New Zealand Plant Protection, 2001)
We undertook field trials to compare differences between ground and raisedset leghold traps to measure population abundance of the brushtail possum (Trichosurus vulpecula) We discuss the observed differences in trap catch rates and the use and potential misuse of a calibration index to correct the raisedset estimates so they can be compared with the groundset estimates